Frances dances - Cooper, Ilene (New York : Bullseye Books, Alfred A. Knopf, 1991)
As she takes ballet lessons and participates in a school play, a timid fourth-grader confronts her fears and learns a lesson about friendship.
School Library Journal.
5.3
5.3
3-6.
3-6
Keywords: Ballet dance -- Fiction; Fear -- Fiction; Friendship -- Fiction; Ballet -- Fiction; Fear -- Fiction; Friendship -- Fiction